Frontotemporal lobar degeneration: old knowledge and new insight into the pathogenetic mechanisms of tau mutations - Rossi, Giacomina; Tagliavini, Fabrizio (Frontiers in Aging Neuroscience, 2015)
Frontotemporal lobar degeneration (FTLD) is a group of heterogeneous neurodegenerative diseases which includes tauopathies. In the central nervous system (CNS) tau is the major microtubule-associated protein (MAP) of neurons, promoting assembly and stabilization of microtubules (MTs) required for morphogenesis and axonal transport. Primary tauopathies are characterized by deposition of abnormal fibrils of tau in neuronal and glial cells, leading to neuronal death, brain atrophy and eventually dementia. In genetic tauopathies mutations of tau gene impair the ability of tau to bind to MTs, alter the normal ratio among tau isoforms and favor fibril formation. Recently, additional functions have been ascribed to tau and different pathogenetic mechanisms are then emerging. In fact, a role of tau in DNA protection and genome stability has been reported and chromosome aberrations have been found associated with tau mutations. Furthermore, newly structurally and functionally characterized mutations have suggested novel pathological features, such as a tendency to form oligomeric rather than fibrillar aggregates. Tau mutations affecting axonal transport and plasma membrane interaction have also been described. In this article, we will review the pathogenetic mechanisms underlying tau mutations, focusing in particular on the less common aspects, so far poorly investigated.